THE TRINITARIAN REFLECTION ON THE PRIMACY OF GOD THE FATHER - Samuel Andri (Diegesis : Jurnal Teologi, 2019)
The article reconsiders the Eastern Christian concept of the Primacy or the Monarchy of God the Father, which has often been deemed as irrelevant and destructive in many modern Trinitarian reflections. For some modern Trinitarian theologians, the hierarchical notion that comes from the idea of the Primacy of God the Father is in complete opposition with the concept of perichoresis, which subvert any forms of hierarchy. Using St. Gregory of Nazianzus’ Theological Oration, the author, however, maintains that the Primacy of God the Father should be preserved, precisely because it provides the foundation for the divine perichoresis to be consistent with Christian monotheistic affirmation.